Urban botanics : an indoor plant guide for modern gardeners - Sibley, Emma (White Lion Publishing, 2021)
"Whether you are looking to cultivate an entire indoor garden, or simply wish to know more about your single cactus, you can be sure to find the right information for you amongst the more than seventy plants in this stylish guide. And the best bit? All the plants are easy to maintain so even the most timid of gardeners can enjoy turning their hand to this green-fingered pastime. Driven by the beautiful artwork of the phenomenally talented Maaike Koster, alongside insightful text from Emma Sibley, co-founder of London Terrariums, each entry offers a concise but complete guide to these plants, telling you their origins, how to care for them and where in your home they will thrive. "--Amazon.